Incidental Paranasal Sinus Abnormalities on MRI Brain and Association with Symptomatic and Asymptomatic Patients - Ahmed, Nisar; Khan, Yasir; Kubra, Khadija tul; Iftikhar, Ammara; Waheed, Sara; Fatima, Khushboo (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate the incidental paranasal sinus findings on magnetic resonance imaging Brain and the association of these findings to the presence of any sinus-related symptoms at the time of scan.Study Design: Comparative cross-sectional study.Place and Duration of Study: Combined Military Hospital, Lahore Pakistan, from Jan to May 2021.Methodology: A total of 135 patients who underwent magnetic resonance imaging of the brain were evaluated for the presence of incidental paranasal sinus abnormalities. The frequency of these abnormalities and their relation with the presence or absence of symptoms was evaluated.Results: One hundred and thirty-two (97.7%) had one or more paranasal sinus abnormalities. Mucosal thickening of 4 mm or more and the presence of polyps are significantly related to the presence of sinus-related symptoms (p-value=0.02).Conclusion: Incidental paranasal sinus abnormalities are a frequent finding on MRI Brain. Mucosal thickening of 4 mm and the presence of polyps appear to be significantly related to the presence of relevant symptoms, while mucosal thickening of less than 3 mm and mucus retention cysts are insignificant.